Relações raciais e racismo na Polícia Militar de Mato Grosso: análise das práticas operacionais da polícia militar e os desafios para a segurança cidadã - Queiróz, Jamil Amorim de (Universidade do Vale do Rio dos Sinos, 2023)
This thesis analyses the subjective and intersubjective meanings and the significant symbols that military police officers attribute to their operational approach activities in racial relations. It aims to understand and analyze the reality of the practices these professionals build in the face of their actions with black individuals. The theoretical-methodological design used was qualitative research from the perspective of George Herbert Mead’s (1933) symbolic interactionism transmitted by Herbert Blumer (1982). This stimulating perspective constitutes the military officers’ comprehension of their social environment. It also understands them as a group member where he is subject to a continual interpretation of meanings. The study participants are military police officers from their training to the moment they apply the knowledge they receive in their operational actions in the public spaces of society. The theoretical categories resulting from the study – training, approach, handcuffing, and military police perception – through analysis as a content analysis technique coexist as a process of interaction. Such process manifests itself with greater emphasis in these actions in the encounter with the black individual as a target of suspicion, producing signifiers that give meaning to the reality of approaches in the context of race relations under the logic of equitable practices. However, the military police officers’ operational practices in their interaction with the black individual have shown racist actions. And these practices constitute interpretations and meanings in the face of approaches in the context of race relations. Regarding the final considerations, we interpret the operational practices of military police officers in the context of race relations as more professional than social characteristics. Such interpretation emphasizes the social bond that is related to the degree of belonging to which the officer belongs, prints cultural attitudes of institutional socialization in these operational approaches, with meanings of actions based on the institution’s sources of how to act about the black individual, and offers evidence of the activation of acts of racism in the impressions of this “foreign” individual. Racism becomes the primary status that affects the way we interact with the black community, where we assess the significance of these interactions with the black population. It also defines an encounter with this black individual and operates as a kind of “social skin” transmitting prejudice and discrimination onto their characters.

La presente tesis analiza los significados subjetivos e intersubjetivos, así como los símbolos significantes que los policías militares, en sus prácticas operacionales, en el contexto de las relaciones raciales, atribuyen a esas actividades de abordaje operacional, cuya finalidad es comprender y analizar la realidad de esas prácticas que estos profesionales construyen, frente a las acciones, junto al individuo negro. El diseño teórico y metodológico utilizado fue la investigación cualitativa bajo la óptica del interaccionismo simbólico que lo caracteriza con el pensamiento de George Herbert Mead (1993), fielmente transmitido por Herbert Blumer (1982). Esa estimulante perspectiva constituye la comprensión del policial militar en su medio social, entendiéndolo como miembro efectivo de su grupo, dentro del cual está sujeto a una continua interpretación de significados. Los participantes del estudio en referencia son policiales militares, desde la formación hasta el momento de aplicar los conocimientos recibidos en sus acciones operacionales en los espacios públicos de la sociedad. Las categorías teóricas resultantes del estudio – formación, abordaje, detención y percepción del policial militar – a través del análisis, en tanto técnica de análisis de contenido, coexisten como proceso de interacción y que en el encuentro con el individuo negro como objeto de sospecha, se manifiesta con mayor énfasis en las acciones, produciendo significantes que dan sentido a la realidad en los abordajes, en el contexto de las relaciones raciales, bajo la lógica de prácticas ecuánimes. No obstante, en las prácticas operacionales de los policiales militares, en la interacción con el individuo negro, hay acciones revestidas de racismo que configuran como interpretación y significados frente a los abordajes en el contexto de relaciones raciales. Las consideraciones finales configuran que las prácticas operacionales de policiales militares en el contexto de relaciones raciales son interpretadas con características más laborales de lo que sociales, enfatizando que el vínculo social está relacionado al grado de pertenencia del grupo social al cual el policial forma parte, imprimiendo, en eses abordajes, actitudes culturales de socialización institucional, con significados de acciones pautadas en las fuentes de institución de como actuar en relación al individuo negro, ofertando evidencias de activación de actos de racismo en las impresiones sobre ese individuo ‘extranjero’. Y, donde se evalúa el significado de esas interacciones con la población negra, en ese caso, el racismo se torna el estatus principal que afecta la manera de la interacción con la comunidad negra definiendo un encuentro con ese individuo negro, que opera como un tipo de ‘piel social’ transmitida sobre sus características el prejuicio y la discriminación.
Keywords: Segurança pública; Polícia militar; Práticas operacionais policiais militares; Preconceito racial; Violência policial; Public security; Military police; Military police operational practices; Racial prejudice; Police violence; Seguridad pública; Practicas operacionales policiales militares; Prejuicio racial; Violencia policial; ACCNPQ::Ciências Humanas::Sociologia